Molecular simulation studies of mea absorption process for CO2 capture - Hon Kit, Lee (2015)
Concentration of CO2 in the atmosphere is increasing rapidly. Emission of CO2 directly impact on global climate change. Monoethanolamine (MEA) absorption process for CO2 capture was developed to combat this trend due to its high reactivity. This allows higher priority absorption for carbon dioxide. The aim of this study is to investigate the intermolecular interaction between the solvent (MEA) and the acid gas (CO2) during the absorption process. Molecular dynamic (MD) simulation will be used to study the molecular interaction and give insight of this process at molecular level. The intermolecular interactions for pure molecules (pure MEA, pure water, and pure CO2), binary system (MEA+CO2, CO2+H2O and MEA+H2O) and tertiary system (MEA+CO2+H2O) at different operating conditions are considered in this study. To perform the molecular dynamic (MD) simulation two boxes of carbon dioxide gas and MEA solvent are combined to study the absorption process. Thermodynamic condition under NVE, NPT and NVT conditions is specified in the simulation. The simulation results are analysed in terms of radical distribution function (rdf) to describe the intermolecular interaction and diffusion coefficient to calculate the solubility factor. Meanwhile, Mean square displacement (MSD) is also used to determine the diffusivity of molecules. The rdf function is plotted on the graph to identify the highest potential molecular interaction at various operating conditions. MD simulation was performed at temperature of 25oC, 40oC, and 45oC to observe the potential interaction of molecules. The trend of rdf graph of each component shows an increasing trend with increase temperature. The purpose of studying primary system is to study the intermolecular interaction of each component on effects of different temperature. A further analysis of binary system was performed to study the intermolecular interaction between MEA molecule and H2O molecule. The rdf graph generated from simulation proved that solubility of MEA in water increase with temperature. Hydroxyl group, –OH of MEA molecule interact with water to form hydrogen bonding bond. Tertiary system of intermolecular interaction is performed to study the CO2 absorption in aqueous MEA solution. It is found that the amine group, -NH of MEA has higher probability to form carbamate ion with carbon dioxide compare to –OH group of MEA. As a references from binary system for tertiary system, higher number of lone pairs in hydroxyl group than amine group of MEA tends to form hydrogen bonds with water.